2016
DOI: 10.1111/sms.12688
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐cultural validity and measurement invariance of the Organizational Stressor Indicator for Sport Performers (OSI‐SP) across three countries

Abstract: Organizational stressors are a universal phenomenon which can be particularly prevalent and problematic for sport performers. In view of their global existence, it is surprising that no studies have examined cross-cultural differences in organizational stressors. One explanation for this is that the Organizational Stressor Indicator for Sport Performers (OSI-SP; Arnold, Fletcher, & Daniels, 2013), which can comprehensively measure the organizational pressures that sport performers have encountered, has not yet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 88 publications
3
12
0
Order By: Relevance
“…Each item is responded to on three separate 6‐point Likert rating scales: frequency (“how often did this pressure place a demand on you?”; 0= never , 5= always ), intensity (“how demanding was this pressure?”; 0= no demand , 5= very high ), and duration (“how long did this pressure place a demand on you for?”; 0= no time , 5= a very long time ). Over a series of studies, Arnold et al . validated the OSI‐SP, providing evidence for its content, concurrent, discriminant, and factorial validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each item is responded to on three separate 6‐point Likert rating scales: frequency (“how often did this pressure place a demand on you?”; 0= never , 5= always ), intensity (“how demanding was this pressure?”; 0= no demand , 5= very high ), and duration (“how long did this pressure place a demand on you for?”; 0= no time , 5= a very long time ). Over a series of studies, Arnold et al . validated the OSI‐SP, providing evidence for its content, concurrent, discriminant, and factorial validity.…”
Section: Methodsmentioning
confidence: 99%
“…"; 0=no time, 5=a very long time). Over a series of studies, Arnold et al 5,31 validated the OSI-SP, providing evidence for its content, concurrent, discriminant, and factorial validity. Support was also provided for the internal consistency of the indicator.…”
Section: Organizational Stressorsmentioning
confidence: 99%
“…Examples of studies focusing on cross-cultural validity using SEM can be found in the literature across a wide array of disciplines. These research fields include pedagogy (Andrews and Diego-Mantecón, 2015; Ay et al , 2015; Tóth-Király et al , 2017), psychology (Camilleri et al , 2015; Saklofske et al , 2016), medicine (Arnold et al , 2017; Joshanloo, 2016), marketing (Raja and Agrawal, 2017) and business (Lukes and Stephan, 2017; Nam et al , 2016; Ralston et al , 2018; Zhu et al , 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Further, investigations of organisational stressors within elite disability football from other countries may offer an opportunity to explore the stressors within different cultures (i.e., Arnold, Ponnusamy, Zhang, & Gucciardi, 2017). Finally, we provide our interpretation of the organisational stressors experienced by international disability footballers.…”
Section: Limitations and Future Researcher Directionsmentioning
confidence: 96%